Construction of novel hypoxia-related gene model for prognosis and tumor microenvironment in endometrial carcinoma - Chen, Junfeng; Wang, Guocheng; Zhang, Donghai; Luo, Xiaomei; Zhang, Da; Zhang, Yongli (Frontiers in Endocrinology, 2022)
Endometrial cancer is currently one of the three most common female reproductive cancers, which seriously threatens women’s lives and health. Hypoxia, as an important clinical feature, disrupts the tumor microenvironment, thereby affecting tumor progression and drug resistance. Therefore, we established a hypoxia-related gene model for risk scores to predict patient prognosis and 1-, 3-, and 5-year overall survival rates. We retrieved the tumor immune gene set and hypoxic marker gene set from TIP and GSEA, respectively. Then, the expression level of hypoxia-related genes and survival data were extracted for comprehensive analysis by Cox regression analysis, and the model was established. We analyzed the survival and prognosis of patients in the high and low-risk groups. We used the Kaplan-Meier method to predict survival curves and ROC to analyze the 1-, 3-, and 5-year survival rates of patients. The Kaplan-Meier curve showed that the low-risk group is associated with a better survival rate. The 1-, 3-, and 5-year AUC values of the model were 0.680, 0.698, and 0.687, respectively. In addition, we investigated the relationship between these model genes and independent prognostic analysis, immune cell infiltration, immune checkpoints, and m6A-related genes. Finally, we found that LAG3 may be a potential immune checkpoint for the treatment of endometrial cancer. In conclusion, we found 4 hypoxia-related genes (ANXA2, AKAP12, NR3C1, and GPI) associated with prognosis. The hypoxia-related gene model can also predict prognostic prediction and immune microenvironment in endometrial cancer.